The Role of the 3′UTR Region in the Regulation of the ACVR1/Alk-2 Gene Expression - Mura, Marzia; Cappato, Serena; Giacopelli, Francesca; Ravazzolo, Roberto; Bocciardi, Renata (PLOS ONE, 2012)
Background The ACVR1/Alk-2 gene, encoding a BMP type I receptor, is mutated in Fibrodysplasia Ossificans Progressiva, a severe form of heterotopic ossification. Regulation of ACVR1/Alk-2 expression, still poorly understood, is likely to be controlled by transcriptional and post-transcriptional mechanisms. In our work, we focused on the functional role of the 3′UTR region of the gene and on microRNAs as possible modulators of the ACVR1/Alk-2 expression. Results The ACVR1/Alk-2 3′UTR region consists of a 1.1 kb sequence harboring several putative, well-conserved binding sites for miRNAs in its proximal half, and AU-rich elements in the distal one, as assessed by bioinformatic analysis. The functional role of this region was tested in presence of transcription inhibitors and in transfection experiments in different cell lines, with a ACVR1/Alk-2-3′UTR reporter construct. By this transfection-based approach, we have also verified that three microRNAs, among those predicted to target ACVR1/Alk-2 gene by in silico analysis, can bind its 3′UTR sequence thereby modulating its expression. Conclusion In this work we demonstrated that the ACVR1/Alk-2 transcript is unstable in presence of inhibitors of transcription. Functional analysis of the 3′UTR region by Luciferase reporter assays showed that it plays an inhibitory role on ACVR1/Alk-2 gene expression. Moreover, we found that specific miRNAs are involved in modulating ACVR1/Alk-2 gene expression as suggested by binding sites prediction in its 3′UTR sequence. In particular, we found that mir148b and mir365 were able to down-regulate ACVR1/Alk-2 expression, whereas mir26a showed a positive effect on its mRNA. Our data contribute to elucidate some of the mechanisms intervening in the modulation of ACVR1/Alk-2 expression. Considering that no specific and effective treatment of FOP is available, clarifying the basic mechanisms of the ACVR1/Alk-2 gene biology may provide means to develop innovative therapeutics approaches.